2007
DOI: 10.1016/j.contraception.2006.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Contraception and fertility plans in a cohort of HIV-positive women in care

Abstract: Objective: To examine determinants of contraceptive use, desired future childbearing, and sterilization regret among HIV-positive women.Methods: 118 HIV-positive women, age 18-46, receiving care at a University HIV Clinic completed a survey on their reproductive history in 2004. We reviewed their medical records for contraception, antiretroviral medications and HIV/AIDS disease markers. We performed descriptive analysis of population characteristics and logistic regression to assess predictors of their desire … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
76
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(90 citation statements)
references
References 17 publications
12
76
2
Order By: Relevance
“…7 A recent American study showed that HAART use was associated with a lower prevalence of fertility desires. 39 Our findings are, however, consistent with those of a recent Canadian study that reported no association between HAART use and childbearing intentions. 40 Potential reasons for our findings may relate to the nature of HAART and HIV care services at the PHRU.…”
Section: Discussionsupporting
confidence: 45%
See 1 more Smart Citation
“…7 A recent American study showed that HAART use was associated with a lower prevalence of fertility desires. 39 Our findings are, however, consistent with those of a recent Canadian study that reported no association between HAART use and childbearing intentions. 40 Potential reasons for our findings may relate to the nature of HAART and HIV care services at the PHRU.…”
Section: Discussionsupporting
confidence: 45%
“…26,40 Consistent with other studies of HIV-positive and HIV-negative women around the world, number of living children and current partnership status were also strongly associated with childbearing intentions. 6,7,39,40,43 Although HAART use did not affect childbearing intentions among HIV-positive women, we did find that HIV-positive women were 60% less likely than were HIV-negative women to report an intention to have (more) children. It is difficult to compare these findings to other settings since we could identify no studies that directly measured differences in childbearing intentions between HIV-negative and HIV-positive women.…”
Section: Discussionmentioning
confidence: 41%
“…Some studies subsequently showed an increase in pregnancy incidence among HIV-infected women (Blair et al, 2004;, and a corresponding decline in terminations (Massad et al, 2004;Townsend et al, 2008). Recent studies in resource-rich settings suggest that around a quarter to a third of HIV-infected women of reproductive age intend to have children in the future, with rates approaching those in the general population (Ogilvie et al, 2007;Myer et al, 2007;Stanwood et al, 2007;Heard et al, 2007). Furthermore some studies in Africa have shown an association between use of HAART and increased fertility intentions (Maier et al, 2009;Cooper et al, 2009).…”
mentioning
confidence: 99%
“…Without treatment, 30% of infants bom to HIV-infected women will become infected during pregnancy, in labour and delivery, or through breastfeeding (UNAIDS, 2008;Info report, 2006). Thus, in view of the UNAIDS Half of the over 40 million people living with HIV/AIDS worldwide are women (Stanwood, Cohn, Heiser, & Pugliese, 2007); the same is true in Canada (HIV/AIDS Epi update, 2010). In Canada, more than 23% of new HIV infections occur in women and 80% of these women are in their childbearing age (Public Health Agency o f Canada 2010; Ogilvie et al, 2007).…”
Section: Background Of Studymentioning
confidence: 99%
“…Young women acquiring HIV through heterosexual contact are the new wave of the epidemic (Stanwood, Cohn, Heiser, & Pugliese, 2007). The advent of HARRT provided the HIV-positive women new opportunities, such as the possibility of parenthood and increased life expectancy (Wagner et al, 2010).…”
Section: Background Of Studymentioning
confidence: 99%